A stability analysis of the static Einstein‐Klein‐Gordon Boson Stars. Issue 1 (4th February 2021) - Suarez Fontanella, Duvier; de Oca, Alenjandro Cabo Montes
Abstract: The stability of the recently proposed static solutions for boson stars is analyzed. These solutions of Einstein‐Klein‐Gordon (EKG) equations are obtained by considering the interaction of a real scalar field with matter. We assume that the inclusion of the scalar field in addition to matter allows one to justify that stability implies that the total mass of the solution should grow when the initial condition for the density of matter at the origin is also increased. Employing numerical values for the static boson star based on a linear relation between the source and the energy density and between this and the pressure, we found the relation that linked the scalar field at the origin with the matter energy density at the same point. We also determine the behavior of the total mass with the matter energy density in the origin by obtaining through this and the weak energy condition two possible ranges for stable solutions of static boson stars.